The promise of power : the origins of democracy in India and autocracy in Pakistan - Tudor, Maya Jessica, 1975- (Cambridge University Press, 2013)
An examination of how, despite similar historical contexts, India became a stable democracy post-independence, whilst Pakistan became an unstable autocracy.